PENGARUH KUALITAS LAYANAN ONLINE PUBLIC ACCESS CATALOG (OPAC) TERHADAP KEPUASAN MAHASISWA UNIVERSITAS NEGERI PADANG - Tiara Aulia; Hade Afriansyah; Irsyad Irsyad; Enceria Damanik (STKIP Pesisir Selatan, 2026)
This study aims to determine the effect of Online Public Access Catalog (OPAC) service quality on student satisfaction at the Library of Universitas Negeri Padang. This research employed a quantitative approach using a descriptive-correlational method. The study involved 103 active students selected using the total sampling technique. Data were collected using a five-point Likert scale questionnaire tested for validity (r count > r table = 0.361) and reliability (Cronbach’s Alpha 0.979 for variable X and 0.975 for variable Y). Data analysis included descriptive statistics (%TCR), normality test, linearity test, simple linear regression, t-test, and coefficient of determination (R²) using SPSS Version 27. The results showed that: (1) OPAC service quality was categorized as “Good” with 82% achievement; (2) student satisfaction was categorized as “Good” with 82% achievement; (3) there was a positive and significant effect of OPAC service quality on student satisfaction, evidenced by t-count = 25.562 > t-table = 1.660 at 0.05 significance level, with regression equation Y = 13.494 + 0.892X. OPAC service quality contributed 86.6% to student satisfaction, while 13.4% was influenced by other variables. This study examines the effect of OPAC service quality on student satisfaction in the context of digital transformation in university libraries, an aspect that remains limitedly explored in previous research, particularly at Universitas Negeri Padang.